THE REPRESENTATION OF THE PANCASILA STUDENT PROFILE IN JUNIOR HIGH SCHOOL INDONESIAN LANGUAGE TEXTBOOKS - Hilma Azmi Azizah; Ahmad Syukron; Siwi Tri Purnani; Kiki Juli Anggoro (LP2M UIN Abdul Muthalib Sangadji Ambon, 2026)
This study aims to describe the Representation of the Pancasila Student Profile in Indonesian language textbooks for junior high school students in grades VII, VIII, and IX. The data of this study consist of words, phrases, sentences, paragraphs, and discourses that contain elements of the Pancasila Student Profile in Indonesian language textbooks for those grade levels. The data collection technique employed in this study is documentation. The research instrument is the researcher, who is equipped with theoretical knowledge of the Pancasila Student Profile. In addition, the researcher uses supporting instruments in the form of data cards containing indicators of the Pancasila Student Profile. These instruments were validated through content validation by experts. Data validity was ensured using peer debriefing techniques. Basically, the Representation of the Pancasila Student Profile in Indonesian textbooks is carried out because it is still limited, this makes this research a theoretical and practical contribution to the teaching materials of the Independent Curriculum to strengthen the integration of the values of the Pancasila Student Profile. The data analysis in this study employs an interactive analysis model. The results of this study indicate that Indonesian language textbooks at the junior high school level contain the of the Pancasila Student Profile, which includes the following dimensions: (1) faith in and devotion to God Almighty, and noble character; (2) global diversity; (3) mutual cooperation; (4) independence; (5) critical reasoning; and (6) creativity.